Riparian Microtopography Affects Event‐Driven Stream DOC Concentrations and DOM Quality in a Forested Headwater Catchment. Issue 12 (21st December 2022) - Blaurock, Katharina; Garthen, Phil; da Silva, Maria P.; Beudert, Burkhard; Gilfedder, Benjamin S.; Fleckenstein, Jan H.; Peiffer, Stefan; Lechtenfeld, Oliver J.; Hopp, Luisa
Abstract: The transport of dissolved organic carbon (DOC) from the soils to inland waters plays an important role in the global carbon cycle. Widespread increases in DOC concentrations have been observed in surface waters over the last few decades, affecting carbon balances, ecosystem functioning and drinking water treatment. However, the primary hydrological controls on DOC mobilization are still uncertain. The aim of this study was to investigate the role of microtopography in the riparian zone for DOC export and DOM quality. DOC concentration and DOM quality in the shallow groundwater of a riparian zone and in streamflow in a forested headwater catchment was investigated using fluorescence and absorbance characteristics. We found higher DOC concentrations with a higher aromaticity in the microtopographical depressions, which were influenced by highly dynamic shallow groundwater levels, than in the flat forest soil. As a result of the frequent wet‐dry cycles in the upper soil layers, aromatic DOC accumulated in the shallow groundwater within and below the microtopographical depressions. Rising groundwater levels during precipitation events led to the connection of the microtopographical depressions to the stream, resulting in a change toward more aromatic DOC in the stream. Increasing stream DOC concentrations were accompanied by increasing concentrations of iron and aluminum, suggesting the coupled release of these metals with DOC from the riparian zone. Our results highlight the importance of the interplay between microtopography and groundwater level dynamics in the riparian zone for DOC export from headwater catchments. Plain Language Summary: Dissolved organic carbon (DOC) is the result of the continuous breakdown of organic material, such as leaves. It accumulates in the soil and is transported to streams mainly during precipitation events. In this study, we analyzed the shallow groundwater of two differing sites in the Bavarian Forest National Park. Both sites were located close to the stream, but one was characterized by typical forest soil and one by small ponds, which were occasionally filled with water. The site with ponds showed much higher DOC concentrations and the DOC was chemically different from the other site. During a precipitation event, we observed a shift in chemical composition of stream water parameters toward the chemical characteristics found at the site with ponds. Therefore, we conclude that the ponds contribute substantially to DOC mobilization, once they fill with water and get connected to the stream. Key Points: This study found small‐scale differences in dissolved organic carbon (DOC) concentrations and dissolved organic matter (DOM) quality in the riparian zone Microtopographical depressions were characterized by high DOC concentrations and aromatic DOC In‐stream DOC concentrations and DOM quality during a precipitation event resembled shallow groundwater below microtopographical depressions